Criminological Review of Former Drug Users: What is the Potential of the Evil Characteristics? - Amanda, Abraham; Sanjaya, Andika Bangun; Adhi, Gilang Bhaskara; Pambudi, Kukuh (Law Research Review Quarterly, 2020)
One of the efforts to overcome the problem of drug abuse is rehabilitation. In accordance with Article 54 of Law Number 35 of 2009 concerning Narcotics, emphasized that narcotics-addicts and victims of narcotics abuse are obliged to undergo medical rehabilitation and social rehabilitation. This paper tries to examine and analyses how the implementation of drug rehabilitation at the Rumah Damai Foundation, what are the factors that make people fall into drugs, how is the process of drug abuse, what are the causes of drug abuse, and the impact of drug abuse. The subjects of this research consisted of drug abusers who became clients and drug rehabilitation officers as well. Collecting data by interview, observation, and documentation. The data validity used source and method triangulation. Data analysis techniques are data collection, data reduction, data presentation and drawing conclusions. The research highlighted and showed that narcotics or drug abuse is currently very dangerous and has become a problem for the world community, as well as our society. Drugs can be said to be a source of social problems because they have a very bad impact on the continuity of a nation's generation. Apart from external influences there are also internal influences in drug abuse. Based on existing and widely conducted studies, drug abuse by individual drug addicts is indeed influenced by the weak link between individuals and community social control and the existence of an intimate learning process in drug user groups.